Struktura osobowości użytkownika komputera z perspektywy analizy transakcyjnej - Łęski, Zbigniew (Edukacyjna Analiza Transakcyjna, 2015)
The article presents an attempt to use an egogram as a research tool for examining personality structure of computer users. The survey sample consisted of 189 respondents. The analysis con- cerned interdependency between the average level of the structure of the subjects’ ego-states and such variables as the declared level of computer skills, work with office software, playing comput- er games, using social networking sites, communicating with the help of the computer, online shopping, sending, sharing and downloading files, watching films, listening to music, searching for current information, searching for gossips and oddities, as well as activities connected with ex- panding one’s knowledge. The participants of the study were asked to select the timescale for a given activity during the day.